A Survey of Physical Education Teachers' Perceptions of the Utilization of Artificial Intelligence (AI) in the Learning Process - zulheri (Jurnal Humaniora Pendidikan (JHP), 2026)
This study aims to analyze Physical Education, Sports, and Health (PJOK) teachers’ perceptions of the use of Artificial Intelligence (AI) in the learning process in the digital era. This research employed a quantitative approach using a survey method. The sample consisted of 68 PJOK teachers from junior and senior high schools in Banda Aceh, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistics.The results show that teachers’ perceptions of AI utilization are at a high level, with an overall mean score of 3.89. Teachers hold positive views regarding the benefits of AI in improving learning effectiveness, supporting assessment processes, and enhancing the development of interactive learning media. However, several challenges were identified, including limited technological facilities, unstable internet access, and insufficient training on AI integration in schools. Overall, the study concludes that PJOK teachers demonstrate a relatively good level of readiness to adopt AI in learning, although further support in terms of infrastructure and digital literacy enhancement is required to optimize AI implementation in education